BRAIDED RIVER FACIES MODEL OF EARLY CRETACEOUS SEDIMENTS (UPPER BIMA) MEMBER FROM THE YOLA SUB-BASIN, NORTHERN BENUE TROUGH, NE NIGERIA - SARKIYANDOKA, BABANGIDA M. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2020)
Facies model was conducted on the Early Cretaceous sediments of Upper Bima Member from Yola Sub-basin of the Northern Benue Trough, northeastern Nigeria with an objective of interpreting the depositional setting and paleoenvironments. The sedimentary logs/sections compriseof the two (2) main facies associations; the pebbly-sandy and the sandy-silty associations. The sediments were interpreted as deposition in channel and floodplain complex of the braided river depositional system. This formed the basis for reconstructing the depositional framework of the Upper Bima Member in Yola Sub-basin as braided river facies model. The findings however, supported the earlier interpretations from the neighbouring sediments of Bima Formation from the Gongola Sub-basin. It also supports the two endmember sub-division for the Cretaceous sequences of Bima Formation.